Investigation of different sodium hypochlorite volumes, concentrations and times of irrigation in endodontic therapy: a systematic review - Arruda, José Alcides Almeida de; Schuch, Lauren Frenzel; Pereira, Adzo; Monteiro, João Luiz Gomes Carneiro; Melo-Júnior, Paulo Maurício Reis; Mesquita, Ricardo Alves; Moreno, Amália; Callou, Gerhilde (ARCHIVES OF HEALTH INVESTIGATION, 2019)
Although the sodium hypochlorite (NaOCl) solution has been part of the endodontic arsenal for more than one century, current investigations have been unable to determine which NaOCl volume and concentration or which time of application are able to dissolve organic matter without weakening the dental structure during the phase of biomechanical preparation of the root canal. Thus, the objective of the present study was to conduct a systematic literature review with no restriction of publication year or language in order to resolve these questions. The search strategy included the following databases: PubMed, LILACS, Web of Science and ClinicalTrials.gov, and only in vivo human clinical trials were included in the final review. After the removal of duplicates, the systematic literature review yielded 3,717 articles. Of these, 3,685 were excluded after applying the exclusion criteria (ex vivo studies, animal studies, cell-culture studies, narrative review, and studies with no available full texts). A total of 32 full-text articles were assessed for eligibility. After evaluating the full text, all articles were excluded for different reasons. No studies fulfilled our inclusion criteria. This review was unable to answer what time of irrigation, concentration or volume of NaOCl solution can be of maximum effectiveness in endodontic treatment without producing significant changes in the mechanical properties of dentin. Thus, future human clinical studies are needed in order to resolve these questions. Descriptors: Endodontics; Sodium Hypochlorite; Review. Referências Siqueira JF Jr, Guimarães-Pinto T, Rôças IN. Effects of chemomechanical preparation with 2.5% sodium hypochlorite and intracanal medication with calcium hydroxide on cultivable bacteria in infected root canals. J Endod. 2007;33(7):800-5. Brito PR, Souza LC, Machado de Oliveira JC, Alves FR, De-Deus G, Lopes HP et al. Comparison of the effectiveness of three irrigation techniques in reducing intracanal Enterococcus faecalis populations: an in vitro study. J Endod. 2009;35(10):1422-27. Baker NA, Eleazer PD, Averbach RE, Seltzer S. Scanning electron microscopic study of the efficacy of various irrigating solutions. J Endod. 1975; 1(4):127-35. Bystrom A, Happonen RP, Sjogren U, Sundqvist G. Healing of periapical lesions of pulpless teeth after endodontic treatment with controlled asepsis. Endod Dent Traumatol. 1987;3(2):58-63. Zehnder M. Root canal irrigants. J Endod. 2006; 32(5):389-98. Türkün M, Cengiz T. The effects of sodium hypochlorite and calcium hydroxide on tissue dissolution and root canal cleanliness. Inter Endod J. 1997;30(5):335-42. Naenni N, Thoma K, Zehnder M. Soft tissue dissolution capacity of currently used and potential endodontic irrigants. J Endod. 2004; 30(11):785-87. Clarkson RM, Moule AJ, Podlich H, Kellaway R, Macfariane R, Lewis D. Dissolution of porcine incisor pulps in sodium hypochlorite solutions of varying compositions and concentrations. Aust Dent J. 2006;51(3):245-51. Siqueira JF Jr, Rôças IN, Favieri A, Lima KC. Chemomechanical reduction of the bacterial population in the root canal after instrumentation and irrigation with 1%, 2.5%, and 5.25% sodium hypochlorite. J Endod. 2000;26(6):331-34. Gu LS, Huang XQ, Griffin B, Bergeron BR, Pashley DH, Niu LN et al. Primum non nocere - The effects of sodium hypochlorite on dentin as used in endodontics. Acta Biomater. 2017; 61:144-56. Barreto MS, Moraes Rdo A, Rosa RA, Moreira CH, Só MV, Bier CA. Vertical root fractures and dentin defects: effects of root canal preparation, filling, and mechanical cycling. J Endod. 2012; 38(8):1135-39. Chai H, Tamse A. The effect of isthmus on vertical root fracture in endodontically treated teeth. J Endod. 2015;41(9):1515-19. Moher D, Liberati A, Tetzlaff J, Altman DG, PRISMA Group. Preferred reporting items for systematic reviews and meta-analyses: the PRISMA statement. J Clin Epidemiol. 2009;62(10):1006-12. Hand RE, Smith ML, Harrison JW. Analysis of the effect of dilution on the necrotic tissue dissolution property of sodium hypochlorite. J Endod. 1978;4(2):60-4. Thé SD. The solvent action of sodium hypochlorite on fixed and unfixed necrotic tissue. Oral Surg Oral Med Oral Pathol. 1979;47(6):558-61. Ringel AM, Patterson SS, Newton CW, Miller CH, Mulhern JM. In vivo evaluation of chlorhexidine gluconate solution and sodium hypochlorite solution as root canal irrigants. J Endod.1982;8(5):200-4. Ercan E, Ozekinci T, Atakul F, Gül K. Antibacterial activity of 2% chlorhexidine gluconate and 5.25% sodium hypochlorite in infected root canal: in vivo study. J Endod.2004;30(2):84-7. Siqueira JF Jr, Rôças IN, Paiva SS, Guimarães-Pinto T, Magalhães KM, Lima KC. Bacteriologic investigation of the effects of sodium hypochlorite and chlorhexidine during the endodontic treatment of teeth with apical periodontitis. Oral Surg Oral Med Oral Pathol Oral Radiol Endod. 2007;104(1),122–30. Estrela C, Silva JA, de Alencar AH, Leles CR, Decurcio DA. Efficacy of sodium hypochlorite and chlorhexidine against Enterococcus faecalis–a systematic review. J Appl Oral Sci.2008;16(6):364-68. Fedorowicz Z, Sequeira P. Efficacy of sodium hypochlorite and chlorhexidine against Enterococcus faecalis–a systematic review. J Appl Oral Sci.2008;16(6):364-68. Gomes BP, Martinho FC, Vianna ME. Comparison of 2.5% sodium hypochlorite and 2% chlorhexidine gel on oral bacterial lipopolysaccharide reduction from primarily infected root canals. J Endod; 2009;35(10):1350-53. Abbaszadegan A, Khayat A, Motamedifar M. Comparison of antimicrobial efficacy of IKI and NaOCl irrigants in infected root canals: an in vivo study. Iran Endod J.2010;5(3):101-6. Bashetty K, Hegde J. Comparison of 2% chlorhexidine and 5.25% sodium hypochlorite irrigating solutions on postoperative pain: a randomized clinical trial. Indian J Dent Res.2010;21(4):523-27. Haapasalo M, Shen Y, Qian W, Gao Y. Irrigation in endodontics. Dent Clin North Am. 2010;54(2):291-312. Huffaker SK, Safavi K, Spangberg LS, Kaufman B. Influence of a passive sonic irrigation system on the elimination of bacteria from root canal systems: a clinical study. J Endod. 2010;36(8):1315-18. Kandaswamy D, Venkateshbabu N. Root canal irrigants. J cons dent.2010;13(4),256-64. Kaya S, Yiğit-Özer S, Adigüzel O. Evaluation of radicular dentin erosion and smear layer removal capacity of self-adjusting file using different concentrations of sodium hypochlorite as an initial irrigant. Oral Surg Oral Med Oral Pathol Oral Radiol and Endod.2011;112(4):524-30. Paudel KR, Jaiswal A, Parajuli U, Bajracharya M. Different pharmacological solutions in intracanal irrigation. Nepal Med Coll J. 2011;13(2):111-14. Rôças IN, Siqueira JF Jr. Comparison of the in vivo antimicrobial effectiveness of sodium hypochlorite and chlorhexidine used as root canal irrigants: a molecular microbiology study. J Endod.2011;37(2):143-50. van der Vyver PJ, Botha FS, de Wet FA. Antimicrobial efficacy of nine different root canal irrigation solutions. SADJ. 2014;69(4):158-60,162-65. Beus C, Safavi K, Stratton J, Kaufman B (2012) Comparison of the effect of two endodontic irrigation protocols on the elimination of bacteria from root canal system: a prospective, randomized clinical trial. J Endod. 2012; 38(11):1479-83. Keenan AV. No evidence favouring one irrigant versus another in root canal treatments. Evid Based Dent.2012;13(4):107. Pawar R, Alqaied A, Safavi K, Boyko J, Kaufman B. Influence of an apical negative pressure irrigation system on bacterial elimination during endodontic therapy: a prospective randomized clinical study. J Endod.2012;38(9):1177–81. Cohenca N, Paranjpe A, Heilborn C, Johnson JD. Antimicrobial efficacy of two irrigation techniques in tapered and non-tapered canal preparations. A randomized controlled clinical trial. Quintessence Int. 2013;44(3):217-28. Guo X, Miao H, Li L, Zhang S, Zhou D, Lu Y, Wu L. Efficacy of four different irrigation techniques combined with 60 °C 3% sodium hypochlorite and 17% EDTA in smear layer removal. BMC Oral Health. 2014;14:114. Mashalkar S, Pawar MG, Kolhe S, Jain DT. Comparative evaluation of root canal disinfection by conventional method and laser: an in vivo study. Niger J Clin Pract. 2014;17(1):67-74. Martins MR, Carvalho MF, Pina-Vaz I, Capelas JA, Martins MA, Gutknecht N. Outcome of Er,Cr:YSGG laser-assisted treatment of teeth with apical periodontitis: a blind randomized clinical trial. Photomed Laser Surg. 2014;32(1):3-9. Ma J, Tong Z, Ling J, Liu H, Wei X. The effects of sodium hypochlorite and chlorhexidine irrigants on the antibacterial activities of alkaline media against Enterococcus faecalis. Arch Oral Biol.2015;60(7):1075-81. Podar R, Kulkarni GP, Dadu SS, Singh S, Singh SH. In vivo antimicrobial efficacy of 6% Morinda citrifolia, Azadirachta indica, and 3% sodium hypochlorite as root canal irrigants. Eur J Dent.2015;9(4):529-34. Arias-Moliz MT, Morago A, Ordinola-Zapata R, Ferrer-Luque CM, Ruiz-Linares M, Baca P. Effects of dentin debris on the antimicrobial properties of sodium hypochlorite and etidronic acid. J Endod. 2016;42(2):771-75. Rôças IN, Provenzano JC, Neves MA, Siqueira JF Jr. Disinfecting effects of rotary instrumentation with either 2.5% sodium hypochlorite or 2% chlorhexidine as the main irrigant: a randomized clinical study. J Endod. 2016;42(6):943–47. Kist S, Kollmuss M, Jung J, Schubert S, Hickel R, Huth KC. Comparison of ozone gas and sodium hypochlorite/chlorhexidine two-visit disinfection protocols in treating apical periodontitis: a randomized controlled clinical trial. Clin Oral Investig. 2017;21(4):995-1005. Nourzadeh M, Amini A, Fakoor F, Raoof M, Sharififar F. Comparative antimicrobial efficacy of Eucalyptus Galbie and Myrtus Communis L. extracts, chlorhexidine and sodium hypochlorite against Enterococcus Faecalis. Iran Endod J.2017.12(2):205-10. Dakin HD. On the use of certain antiseptic substances in the treatment of infected wounds. Br Med J. 1915; 2(2852):318-20. Walker A. A definite and dependable therapy for pulpless teeth. J Am Dent Assoc. 1922;23(8):1418-25. Grossman LI. Irrigation of root canals. J Am Dent Assoc. 1943;30:1915-17. Bajaj D, Sundaram N, Nazari A, Arola D. Age, dehydration and fatigue crack growth in dentin. Biomaterials. 2006;27(11):2507-17. Kruzic JJ, Nalla RK, Kinney JH, Ritchie RO. Crack blunting, crack bridging and resistance-curve fracture mechanics in dentin: effect of hydration. Biomaterials. 2003;24(28):5209-21. Martins JNR, Marques D, Francisco H, Caramês J. Gender influence on the number of roots and root canal system configuration in human permanent teeth of a Portuguese subpopulation. Quintessence Int. 2018;49(2):103-11. Zehnder M, Schmidlin P, Sener B, Waltimo T. Chelation in root canal therapy reconsidered. J Endod. 2005;31(11):817-20. Marending M, Luder HU, Brunner TJ, Knecht S, Stark WJ, Zehnder M. Effect of sodium hypochlorite on human root dentine-mechanical, chemical and structural evaluation. Int Endod J. 2007;40(10):786-93. Aslantas EE, Buzoglu HD, Altundasar E, Serper A. Effect of EDTA, sodium hypochlorite, and chlorhexidine gluconate with or without surface modifiers on dentin microhardness. J Endod. 2014;40(6):876-79. Siqueira JF Jr, Machado AG, Silveira RM, Lopes HP, de Uzeda M. Evaluation of the effectiveness of sodium hypochlorite used with three irrigation methods in the elimination of Enterococcus faecalis from the root canal, in vitro. Int Endod J. 1997;30(4):279-82. Hertel M, Sommer K, Kostka E, Imiolczyk SM, Ballout H, Preissner S. Outcomes of endodontic therapy comparing conventional sodium hypochlorite irrigation with passive ultrasonic irrigation using sodium hypochlorite and ethylenediaminetetraacetate. A retrospective analysis. Open Dent J. 2016;10:375-81. Soares JA, Pires Júnior DR. Influence of sodium hypochlorite-based irrigants on the susceptibility of intracanal microbiota to biomechanical preparation. Braz Dent J. 2006;17(4):310-6.